Analytical and experimental techniques for chatter prediction, suppression and avoidance in turning: literature survey - Mohammad, Alzghoul; Sarka, Ferenc; Szabó, J. Ferenc (Design of Machines and Structures, 2024)
Chatter is a self-excited vibration that takes place during turning operations. It is either to be avoided or reduced for its negative impact on the machine-tool, the work-piece surface finish, and the cutting tool life. A lot of research has been carried out in this domain to understand this phenomenon, which leads to finding ways to detect, identify, avoid, reduce, and control chatter in turning processes. In this paper, chatter research re-lated to turning processes is reviewed and summarized. The main goal of this review paper is to compare different chatter prediction, suppression, and avoidance techniques to find out the most effective technique, so a scope of a work related to turning processes chatter is defined.